A new perspective and method for understanding the relationship between characters and words in the Shang dynasty. (June 2020) - Zhu, Shengyu
Relationships between characters and words can be divided into two levels, the relationship among characters and the relationship among words – one of the core problems in Chinese philology. The relationships in Oracle Bone Inscriptions (OBIs) are very complicated due to the diversity of the configurations of graphs and the unclearness of phonetic information, which cause great difficulty in the study of these relationships, including whether characters are variants or have distinct meanings. OBIs have their own particularity, namely, a high degree of hieroglyphics. When studying the relationship between characters and words in OBIs, we are limited to actual divination materials and exploration of characters' design intention. In this regard, relevant theories and methods in cognitive linguistics provide reference. In terms of characters, graphemes in the lao 牢-set, xian 陷-set, zhu 逐-set, kan 坎-set and che 车-set are visually distinct, but in terms of language are variants representing one word.